TEACHERS ACCEPTANCE AND INTENTION TO USE ICT IN LEARNING - Kurniabudi, Kurniabudi (LLDIKTI Wilayah X, 2018)
Although ICT could bring many benefit in learning ,however implementation of ICT in the learning process is not easy. In fact, adoption of ICT in learning, is not only occurs in higher education but also in schools. The aim of This study is to identify the impact of Subjective Norm, Image and Computer Self-Efficacy against the behavior of teachers in using ICT in learning.Technology Acceptance Models (TAM) 2 used in the analysis of the behavior of the reception. Data was collected from high school teachers in the city of Jambi. Data were analyzed using SEM method with applications SmartPLS.This study reveals that the consistency of Perceived Usefulness and Perceived Ease of Use has a direct influence on Intention to Use . Subjective Norm and Image provides indirect influence on Intention to Use Computer Self - Efficacy whereas no effect on of Perceived Usefulness , Perceived Ease of Use and Intention to Use